Synergistic effects of ultrasonic vibration and nanofluid-MQL on surface integrity in sustainable machining of Ti-6Al-7Nb alloy - Duman, Erkin; Yapan, Yusuf Furkan; Uysal, Alper (ELSEVIER, 2025)
Recent trends in the biomedical industry emphasize improving the surface properties of materials for better biocompatibility. Consequently, various surface modification techniques, including machining, are used on titanium bioimplants. This study investigates the impact of sustainable machining on the surface integrity of the Ti-6Al-7Nb biomedical alloy under various cutting conditions including conventional dry cutting, minimum quantity lubrication (MQL), graphene nanofluid-based MQL (N-MQL), and ultrasonic vibration-assisted machining (UVA), encompassing UVA-DRY, UVA-MQL, and UVA-N-MQL. The focus is to analyze the relationship between machining performance and surface integrity. Machining experiments first evaluated cutting forces, cutting temperatures, and chip morphology. Then, surface roughness, texture, microstructural changes, microhardness, and phase transformation were examined to assess surface integrity. The findings reveal that the UVA-N-MQL significantly reduces cutting forces (by up to 6 % for main cutting force and 10.4 % for thrust force) and cutting temperatures (by up to 29 % compared to dry cutting), while enhancing chip breakability. These outcomes stem from the synergistic interaction between the ultrasonic softening effect induced by highfrequency tool oscillations and the enhanced coolant/lubricant penetration enabled by N-MQL lubrication. Additionally, surface roughness was minimized by up to 57 % with UVA-MQL, resulting in the smoothest surface finish. Microstructure analysis also indicated that dry cutting produced the deepest deformation layer (29.5 mu m), while UVA-N-MQL achieved the shallowest affected zone (9.5 mu m). Subsurface hardness exhibited a notable increase within a depth range of 60-80 mu m, with dry cutting demonstrating the most significant work hardening (a 12 % increase), in contrast to UVA-MQL, which experienced the least. Phase transformation analysis revealed a significant increase in the (3 phase ratio due to machining, with conventional turning exhibiting higher transformation than UVA machining. The UVA-N-MQL method resulted in 10.4 % less phase transformation compared to conventional dry cutting.
Keywords: Microstructure deformation; Microhardness; Surface texture; Phase transformation; CUTTING FLUIDS; CHIP FORMATION; WEAR; TITANIUM; PARAMETERS; METALS; SIZE; MICROSTRUCTURE; PLASTICITY; MORPHOLOGY; Engineering